2021
DOI: 10.25081/cb.2021.v12.6608
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic potential of Gamma rays on Somatic cell division and morphological parameters in Foeniculum vulgare Mill.

Abstract: Mutagenesis involving ionizing radiation has been widely used for alteration in genetic constituents to increase the variability at gene level in a very small fraction of time. But, attempts to induce genetic variability in fennel for agronomically important trait are very limited. Narrow genetic base is the main hindrance in handling the conventional breeding in Fennel . Thus, main idea of this study is to generate genetic variability in Ajmer fennel-2 variety of Foeniculum vulgare Mill. by using the most pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…The plants treated with 60 Gy produced the fewest flowers and took the longest to flower for the first time. These findings are consistent with those of Bharathi et al (2013), Singh et al (2017, and Kumar and Mishra (2021). They found that increasing the gamma irradiation dose causes plants to take longer to produce flower buds and enter a generative phase.…”
Section: Quantitative Morphological Characterssupporting
confidence: 93%
“…The plants treated with 60 Gy produced the fewest flowers and took the longest to flower for the first time. These findings are consistent with those of Bharathi et al (2013), Singh et al (2017, and Kumar and Mishra (2021). They found that increasing the gamma irradiation dose causes plants to take longer to produce flower buds and enter a generative phase.…”
Section: Quantitative Morphological Characterssupporting
confidence: 93%